THE ROLE OF CONSUMER TRUST IN MEDIATING THE INFLUENCE OF LIVE STREAMING SHOPPING ON PURCHASE DECISIONS IN THE SHOPEE APPLICATION (Study of Generation Z Shopee Live Users in Denpasar City) - Tria Audina; I Gede Nandya Oktora P (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
The development of information and communication technology has driven the rapid growth of e-commerce, changing the way people shop. Shopee, as one of the largest e-commerce platforms in Indonesia, has presented innovation through the Shopee Live feature, which allows direct interaction between sellers and buyers via live streaming to encourage consumer purchasing decisions. Live streaming offers consumers an interactive and real- time shopping experience with sellers who are able to increase consumer confidence in the products offered. This research aims to understand the influence of live streaming shopping on purchasing decisions and the role of consumer trust as a mediating variable in the Shopee e-commerce context, especially in Denpasar City. This research involved 112 generation Z respondents who were Shopee Live users in Denpasar City. The data collection method was carried out through an online questionnaire, and the data was analyzed using path analysis, Sobel test, and VAF (Variance Accounted For) test. The research results show that live streaming shopping has a positive and significant effect on purchasing decisions and consumer trust. Consumer trust also has a positive and significant influence on purchasing decisions, and successfully mediates some of the influence of live streaming shopping on purchasing decisions. These results provide insight for e-commerce business players to develop effective marketing strategies by utilizing live streaming shopping features and building consumer trust to increase purchasing decisions.